Law Enforcement In Cases Of Criminal Domestic Violence ( KDRT ) Within The TNI - Arief Fahmi Lubis (International Journal of Law and Society, 2024)
In accordance with the application of the principle of equality before the law, if criminal behavior occurs against a soldier's wife, the punishment imposed on her husband as a TNI soldier will be the same as that applied in the General Court. The aim of this research is to show that in the context of law enforcement as guidance within the TNI, in domestic violence cases many military members are charged with criminal sanctions by Military Judges. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description at the time of the research. The results of this research show that The aim of the Panel of Judges in imposing sentences is not merely to convict people who commit criminal acts but also has the aim of educating so that the person concerned can return to the right path to become a good citizen and soldier in accordance with the Pancasila and Sapta Marga philosophies.